Designing an Experiential Marketing Model in the Health Tourism Industry of Iran - Fakur, Aria; Jalali, Seyed Mehdi; Taherikia, Fariz (Business, Marketing, and Finance Open, 2025)
The present study aims to design an experiential marketing model in the health tourism industry of Iran. This research is applied in nature, qualitative in methodology, inductive in approach, and interpretive in paradigm, incorporating theoretical foundations and interviews as the dominant research methods. The research strategy is based on grounded theory, and data collection was conducted accordingly. Interviews were conducted with experts and practitioners in health tourism to identify the factors and components shaping the experiential marketing model in the health tourism industry of Iran, particularly in the sector related to hospitals and medical centers. These interviews were primarily conducted in person (five participants) and, to a lesser extent, by telephone (three participants). Ultimately, the study concluded after conducting interviews with a total of eight participants. The criterion for determining the number of interviews was reaching theoretical saturation, meaning that from the seventh and eighth interviews, no new information emerged regarding the interview topics, thereby achieving theoretical saturation. In total, over 173 minutes of interviews were conducted over approximately three months through coordination with subject matter experts. The collected data from the interviews were analyzed using MAXQDA software. After a thorough examination of all interviews, analysis of participants’ statements and perspectives, and a systematic review of relevant studies, a total of 78 codes were identified in the open coding phase. Following further analysis and categorization, six main categories and fifteen subcategories were identified.